2022
DOI: 10.18280/ijsdp.170117
|View full text |Cite
|
Sign up to set email alerts
|

Policy Strategy for Sustainable Management of Mangrove Ecotourism in Siak Regency, Riau Province, Indonesia

Abstract: Siak regency, Indonesia, has more than two hundred-thousand-hectare mangrove areas. Local community for all this time has been developed mangrove areas as ecotourism, but they still lack sustainable management to maintain it. Therefore, this study aims to promote strategies' policy for the sustainable management of mangrove ecotourism in the Siak regency. The research was conducted from July 2019 to July 2020 at 3 locations of mangrove ecotourism, which involved 30 respondents, consisting of 21 people to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Based on Table 3, it can be seen that the number of species found in Pangkalan Jambi Village is 10 species with a range of 4-7 species per station. This type is less than the number of types of mangrove vegetation found in Dumai Bakau Airport based on research [23] which found 17 types of mangroves and research [24] which found as many as 17 types of mangroves in Riau Coastal as well as [25] who found 17 species in the Rawa Mekar Jaya Siak mangroves. This difference can be caused by damage to mangroves in Pangkalan Jambi Village.…”
Section: Characteristics Of Mangrove Ecosystemsmentioning
confidence: 68%
“…Based on Table 3, it can be seen that the number of species found in Pangkalan Jambi Village is 10 species with a range of 4-7 species per station. This type is less than the number of types of mangrove vegetation found in Dumai Bakau Airport based on research [23] which found 17 types of mangroves and research [24] which found as many as 17 types of mangroves in Riau Coastal as well as [25] who found 17 species in the Rawa Mekar Jaya Siak mangroves. This difference can be caused by damage to mangroves in Pangkalan Jambi Village.…”
Section: Characteristics Of Mangrove Ecosystemsmentioning
confidence: 68%
“…Basyuni et al (2018) underscored that knowledge about mangrove tourism landscapes will enhance understanding of community-based mangrove management in the future. Additionally, Erlinda et al (2022) suggested that developing tourism facilities and infrastructure is a key strategy for the sustainable management of mangrove ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…In the last five years, research on mangrove ecosystem management in Indonesia was carried out in tourist areas, one of which was by Erlinda et al (2022) in producing alternative priority strategic choices in the Rawa and Barembang River ecotourism areas, Siak Regency. His research considered several things: potential, attractiveness, activities, and tourism policies.…”
Section: Mangrove Ecosystem Management In Tourist Areasmentioning
confidence: 99%
“…Interviews and participatory mapping methods were used in the research of Damastuti et al (2022) for the identification of community-based mangrove management (CBMM), which has characteristics in the form of community governance, joint strategies, and supporting regional regulations), as well as management impact components (mangrove cover and diversity of mangrove flora and fauna). Interviews with the combination of SWOT and AHP were also conducted by Erlinda et al (2022) in formulating sustainable ecosystem management strategies, including increasing ecotourism promotion, opening investment opportunities for ecotourism development, improving facilities and infrastructure, providing ecotourism business training, establishing cooperation between the government and stakeholders, and maintaining mangrove ecosystems. The study's findings stated that, in terms of policy, funding is an essential factor that the government and stakeholders must realize to improve the welfare of local communities and the sustainability of mangrove ecosystems in Siak Regency.…”
Section: Mangrove Ecosystem Management With a Qualitative Approachmentioning
confidence: 99%
See 1 more Smart Citation